Axillary dissection in sentinel lymph node positive breast cancer: Is the staging information worthwhile for patients?. Issue 2 (28th August 2019) - Chang, David W.; Bressel, Mathias; Hansen, Carmen; Blinman, Prunella; Schofield, Penelope; Chua, Boon H.
Abstract: Aims: The Z0011 randomized trial demonstrated no significant difference in axillary recurrence rate or survival with or without axillary dissection in patients with a positive sentinel node biopsy. However, there is continuing controversy regarding the generalizability of its results, and axillary dissection provides additional pathologic staging information that may guide adjuvant therapy. Thus, axillary dissection after positive sentinel node biopsy is being further investigated in an actively recruiting randomized trial. We elicited patients' preferences for axillary dissection versus no axillary dissection after positive sentinel node biopsy for early breast cancer. Methods: Patients who had undergone axillary dissection after positive sentinel node biopsy as part of breast conserving therapy were provided with a validated, self‐rated questionnaire. The questionnaire comprised two trade‐off questions to determine the maximum chance of developing arm side‐effects from axillary dissection to justify the benefit of additional axillary staging information. Social, demographic, and clinical details were collected. Results: Ninety‐nine of the 126 eligible patients returned the questionnaire and 76 completed the trade‐off assessment. The median age of participants was 62 years. The median numbers of sentinel and axillary nodes removed were 2 and 12, respectively. Forty‐seven percent of participants had arm swelling or tenderness of any severity. Seventy‐five percent of participants would have axillary dissection even if the chance of arm side‐effects like they had experienced was 100%. Conclusion: Most patients with early breast cancer preferred axillary dissection after positive sentinel node biopsy for the additional staging information even though there was no survival benefit from axillary dissection.